Representation of olympic athletes in a Malaysian online newspaper / Wardah Hajisama - Wardah, Hajisama (2012)
The purpose of this study is to investigate how genders are represented in selected sports news during the 2008 Olympics. The sports news of the 2008 Olympics from The Star online newspaper were selected as the corpus of the study, focusing on reports of selected female-appropraite sports. These female-appropriate sports were classified by Vincent et al. (2002) based on categories proposed by Metheny (1965) and Kane (1988). A discourse analysis was conducted to investigate how gender is portrayed in today’s sports media. A concordance software was used to study the data to obtain terms referring to male and female athletes. Visual images were also analysed to examine how the media portray male and female athletes on the selected articles. Results indicate that female athletes were under-represented in terms of word and photograph count. Although women were competing in the so-called ‘female-appropriate’ sports, they were negatively portrayed compared to their male counterparts. Some of the terms used for women tend to focus on appearance rather than their achievement and skills. Interestingly, the photographs attributed to male athletes were more likely to be featured as being competitive compared to the female counterparts. This study tends to support the notion that gender bias and stereotyping still exist in today’s newspapers reporting of sports.